Hybrid Fourier-domain mode-locked laser for ultra-wideband linearly chirped microwave waveform generation - Jian Tang (Nature Portfolio, 2020)
Linearly chirped microwave waveforms with high time-bandwidth products would have important applications but are difficult to achieve. Here the authors generate such a waveform in a photonic setting by implementing a micro-disk resonator as a tunable optical bandpass filter in a Fourier-domain mode-locked laser.